Stress-Strain Rock State Evaluation Method Around Deep Well - Mykhailovska, Olena; Rubel, Viktoriia; Oleksiienko, Olena; Petruniak, Maryna (International Journal of Engineering and Technology, 2018)
The analysis of the stress-strain state of deep wells in the rocks prone to theÂ complications manifestation has been carried out. Engineering method proposed authors offer use in tactical decision making in designing and wells drilled. Stress-strain rock state evaluation of the borehole zone is performed, which is analyzed using data on the destruction of rock and reservoir pressure, measured in wells. The proposed evaluation method takes into account the relaxation of stresses in the zone near the well. Â The calculations were carried out outside the influence of a rock massif. Based on the calculations by the engineering method, it was discovered that intensive cavern formation with roughness and destruction would occur.Â Â Â